Sense of Place dan Kepuasan Berwisata pada Arsitektur Kampung Budaya Sindang Barang Bogor - Juwono, Sudarmawan; Solo, Adrianus; Ali, Abdullah; Aryanti, Dwi; Andayani, Keti; Adistira, Gagas (LPPM Universitas Bung Karno, 2024)
Sindang Barang Bogor Cultural Kampung is a tourist destination in Bogor which focuses on Sundanese village culture. This tourist destination is managed by the local community by utilizing the existing environmental potential. This community service aims to provide input to the management of Sindang Barang Bogor Cultural Kampung, especially regarding the level of satisfaction felt by tourists. In this measurement, the concept of sense of place is used as a measure of the quality of space that can be felt by the human senses when using space. Meanwhile, tourist satisfaction is a positive response given by tourists regarding their experience with the space object. If these two concepts are connected, sense ofpPlace can be used as an approach to measuring travel satisfaction. The results of the exploration were submitted to management who responded positively as useful suggestions, creative suggestions, basic needs, evaluation materials as input in planning and evaluating the Sindang Barang Cultural Kampung.